2018
DOI: 10.3390/brainsci8030038
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Vitamin E Supplementation in Bladder Function and Spasticity during Spinal Cord Injury

Abstract: Traumatic spinal cord injury (SCI) results in debilitating autonomic dysfunctions, paralysis and significant sensorimotor impairments. A key component of SCI is the generation of free radicals that contributes to the high levels of oxidative stress observed. This study investigates whether dietary supplementation with the antioxidant vitamin E (alpha-tocopherol) improves functional recovery after SCI. Female adult Sprague-Dawley rats were fed either with a normal diet or a dietary regiment supplemented with vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 125 publications
(156 reference statements)
0
10
0
Order By: Relevance
“…In SCI patients, dietary supplementation for 3 months, which included three 750 mg per day of omega-3 fatty acids and antioxidants (400 mg of mixed tocopherols, coenzyme Q10, curcumin, etc. ), caused a decrease of inflammatory cytokines with reduction in neuropathic pain [153]; 2 months vitamin E dietary supplementation 765-1020 IU/day in rats before SCI showed accelerated bladder recovery, significant motor improvement, and a high number of oligodendrocytes compared to the controls [154].…”
Section: Combinatory Therapies and Results In Symptoms Of Scimentioning
confidence: 99%
“…In SCI patients, dietary supplementation for 3 months, which included three 750 mg per day of omega-3 fatty acids and antioxidants (400 mg of mixed tocopherols, coenzyme Q10, curcumin, etc. ), caused a decrease of inflammatory cytokines with reduction in neuropathic pain [153]; 2 months vitamin E dietary supplementation 765-1020 IU/day in rats before SCI showed accelerated bladder recovery, significant motor improvement, and a high number of oligodendrocytes compared to the controls [154].…”
Section: Combinatory Therapies and Results In Symptoms Of Scimentioning
confidence: 99%
“…A recent study demonstrated that α‐tocopherol reduces the triglyceride and cholesterol‐lowering effects of rice bran tocotrienol in rats fed a Western diet (Shibata et al, 2016 ). α‐Tocopherol promotes barrier function and anti‐inflammatory responses by binding to the regulatory domains of protein kinase Cα (PKCα), a regulator and antagonist of heart failure, and decreases the activation of the pro‐inflammatory transcription factor NF‐κB, which results in cytokines and mast cell activation (Cordero et al, 2018 ; Tettamanti et al, 2018 ). Surprisingly, our findings show that α‐tocopherol has no effect on inflammatory factors in normal small intestinal epithelial cells, implying that this increase in tight junction protein expression is irrelevant to the inflammatory pathway under normal healthy conditions.…”
Section: Discussionmentioning
confidence: 99%
“…They have been found to inhibit the expression of proapoptotic proteins (Bax and Caspase-3), increase the level of antiapoptotic protein (Bcl-2), reduce the level of MDA, and improve the activities of SOD and GSH (e.g., CoQ10) [ 236 ]. For example, the rats with SCI treated with vitamin E-enriched diet showed accelerated bladder recovery and improved locomotor function [ 237 ]. Treatment either with β-carotene or lycopene was also shown to reduce oxidative damage, mitochondrial dysfunction, cell apoptosis, and hind limb motor disturbances [ 238 ].…”
Section: Preclinical Studies With Antioxidant Agentsmentioning
confidence: 99%